Efektivitas Konsumsi Putih Telur Ayam (Albumen) Untuk Penyembuhan Luka Perineum Pada Ibu Post Partum Hari Kedua Yang Mengalami Derajat I Dan II Di Klinik Pratama Hj Hanum - Elv Feedia Mona Saragih; Verawaty Fitrinelda Silaban; Alvionita Selvia Ningsih; Elfrida Dakhi; Lidia Ayu Putri; Oktaviani Harahap (LPPM STIKES Siti Hajar dan Insight Power, 2023)
Perineal wounds are tears that occur in the perineum during the delivery process. Perineal tears are wounds or tears in the skin and muscle tissue in the birth canal that occur irregularly. The purpose of this study was to determine the effectiveness of consuming chicken egg whites for healing perineal wounds on the second day of post partum mothers who experienced degrees I and II at the Hj Hanum Primary Clinic. The type of research used is Quasi Experimental Design research. The sample in this study amounted to 30 people. This sampling technique with consecutive sampling technique. Data collection methods in this study are primary data and secondary data. Data analysis will be carried out using univariate analysis and bivariate analysis through the Wilcoxon Signed Ranks Test with a significance of 0.05. The results of the Wilcoxon Signed Ranks Test in the final result obtained p = value 0.000 < α = 0.05 so it can be concluded that there is an influence effectiveness of chicken egg white consumption on perineal wound healing in post partum mothers.Keywords: Egg White, Perineal Wound Healing, Post Partum Mother